1991
DOI: 10.1159/000186214
|View full text |Cite
|
Sign up to set email alerts
|

Protamine Sulfate Induces Enhanced Peritoneal Permeability to Proteins

Abstract: We present a direct link between the neutralization of anionic sites by intraperitoneal protamine and a rise in protein passage to the peritoneal cavity during isosmotic peritoneal dialysis in rabbits. Each experiment included two 1-hour exchanges. No drugs were added in the first exchange. In group A (control) there were no drugs in the second hour either. In group B, protamine (50 μg/ml) was added to the second exchange volume. In group C, protamine and heparin (50 U/ml) were added. In groups A and C, appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…In the present study, we have observed a protein loss of 2-11 g/8 h. This heteroge neity in the peritoneal transport of proteins has been as cribed to constitutional differences in the anatomy and function of the peritoneal membrane among patients such as: microvascular structure [20]; electric charge of the peri toneal membrane [21]; peritoneal mesothelium [22,23]; peritoneal stromal texture [24]; surface area of parietal and visceral peritoneum [23,[25][26][27] and lymphatic absorption [28]. In addition, acquired factors during CAPD have been reported to affect peritoneal permeability to proteins, glu cose absorption rate and ultrafiltration capacity: duration of CAPD [2, 5-7, 29, 30], peritonitis episodes [31][32][33], dialysate composition [30,34] and drug treatment [21,35,36].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In the present study, we have observed a protein loss of 2-11 g/8 h. This heteroge neity in the peritoneal transport of proteins has been as cribed to constitutional differences in the anatomy and function of the peritoneal membrane among patients such as: microvascular structure [20]; electric charge of the peri toneal membrane [21]; peritoneal mesothelium [22,23]; peritoneal stromal texture [24]; surface area of parietal and visceral peritoneum [23,[25][26][27] and lymphatic absorption [28]. In addition, acquired factors during CAPD have been reported to affect peritoneal permeability to proteins, glu cose absorption rate and ultrafiltration capacity: duration of CAPD [2, 5-7, 29, 30], peritonitis episodes [31][32][33], dialysate composition [30,34] and drug treatment [21,35,36].…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, in 6 of our patients with low permeability and in 5 patients with high permeability, studied prospectively, the peritoneal protein concentra tion remained within the limits set for the groups. There fore, we suggest that inherent constitutional factors such as peritoneal surface area, pore number, size and distribu tion, interstitium and capillary ultrastructure, the charge of the peritoneal 'membrane' and lymphatic absorption may be important in determining peritoneal transport in addition to the detrimental effect of long-term dialysis [20,21,23,45,46], Although Paolo et al [47] claim that the morphological changes occurring in the peritoneum dur ing 7-49 months of CAPD are not associated with changes in the peritoneal clearance of small solutes or effluent volume, the continuous depletion of mesothelial phos pholipids with an abundant production of prostacyclins [22] and the nonenzymatic glycosylation of proteins in the peritoneal stroma and basement membrane [24] suggest that both fluid and solute transport may be altered during long-term CAPD [48].…”
Section: Discussionmentioning
confidence: 99%
“…Results are expressed as mean Ϯ SD of four separate experiments. within the mesothelium and the underlying basal lamina by chemical or bacterial injury has also been documented (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Injury to the mesothelium represents an important initiating step, leading to the progressive histologic changes of the peritoneum in peritoneal dialysis (PD). The abundant anionic sites normally present in the mesothelium and the underlying basement membrane prevent excessive albumin wastage (5)(6)(7)(8). Proteoglycans (PG), which are anionic macromolecules present ubiquitously on the cell surface and in basement membrane (9,10), are putatively major contributors to the anionic sites in the peritoneum.…”
mentioning
confidence: 99%
“…Previously we found no indication that the electric charge of a macromolecule is a determinant of its transperitoneal transport rate [9,10]. Other studies indicated that negatively charged macromolecules are retarded in their passage across the peritoneal membrane [11,12], but the opposite has also been found using neutral and charged dextrans [13].…”
Section: Introductionmentioning
confidence: 68%